Interface inhibitory action on Interleukin-1β using selected anti-inflammatory compounds to mitigate the depression: A computational investigation. (December 2022) - Sardar, Madiha; Zia, Komal; Ashraf, Sajda; Malik, Hira Noor; Jabeen, Almas; Khan, Khalid Mohammed; Ul-Haq, Zaheer
Abstract: Interleukin-1β (IL1β) is a keynote mediator of inflammation with diverse physiological functions, playing a fundamental role in memory and mood regulation. The pleiotropic effects of IL-1β have been proposed to be implicated in the pathogenesis and etiology of depression. Thus, targeting IL-1β offers an inimitable opportunity to develop new strategies for an alternative therapy to treat depression. The focus of this study is to find out the potential inhibitors against IL-1β. Since, there is no oral specific drug reported yet thus, demanding an urgent need to develop new immunomodulatory drugs to combat chronic diseases. In this study, ligand-based pharmacophore modeling integrated with virtual screening and molecular docking strategy was designed to identify novel compounds capable of inhibiting the interactions towards cognitive receptor IL-1RI. In this connection, a set of 30, 000 compounds were screened by a developed pharmacophore model that led to the retrieval of 2043 molecules from the in-house library and ZINC Database. Primarily, specific binding regions for IL-1β inhibitors have been explored by blind docking studies. After the selection of the binding site, the hits identified as actives based on the 3D-pharmacophore model were assessed by molecular docking studies. In a stepwise screening, six potential virtual hits were shortlisted for molecular dynamic simulation to acquire insights into their dynamic behavior. The obtained results highlighted that these compounds are stabilized in the targeted pocket of IL-1β and possibly block the formation of an active heterocomplex, subsequently locking the associated signaling cascade. Further in vitro experiments confirmed the inhibitory potential of Compound-157 and compound-283 with the IC50 of 1.6 ± 0.1 and 9.1 ± 1.7 µg/mL respectively. Graphical Abstract: ga1 Highlights: The study encompasses of Ligand-Based pharmacophore modelling, docking simulation and mechanistic analysis. Interfacial key residues were identified to design IL-1β/IL-1RI potential inhibitors. The mechanistic results highlighted that shortlisted six virtual hits are stabilized in the targeted pocket of IL-1β and possibly block the formation of active heterocomplex. IL-1β inhibitors are found in good agreement withexperimental studies.